Taxonomy and Antimicrobial Activity of Gliding Bacterium from Indonesian Mangroves - Senlie Octaviana; Tjandrawati Mozef; Joachim Wink (HAYATI Journal of Biosciences, 2022)
The discovery of new antibiotic is needed, due to the increasing antimicrobial resistance in nature. Therefore, this study aims to isolate gliding bacteria and to ascertain their antimicrobial activity against pathogenic microbes. This research was conducted by isolating gliding bacteria from mangrove sediment in Muara Angke, North Jakarta, Indonesia. All of the strains were identified by 16S rRNA genes sequencing and those selected strain was characterized using polyphasic approach. The performance of crude extracts against to ten pathogenic microorganisms were detected using serial dilution test in 96-well plates. Mangrove gliding bacteria isolates designated 313MSO and 314MSO were showed high homology to Ohtaekwangia kribbensis with 96.20% and 99.12% similarity, respectively. The polyphasic approach led to the conclusion that the strain 313MSO was a new species of the genus Ohtaekwangia. Twenty-three crude extracts were obtained from cultivating the strain in twenty-three different media. The most of them inhibited the growth of Staphylococcus aureus Newman with the minimum concentration of 33.33-66.67 µg/ml. Four compounds (Marinoquinolines A-D) were obtained from HPLC-MS analysis. Furthermore, the strain 313MSO is presently being studied for in-depth identification of additional unknown metabolites detected in the crude extracts.